Genome-Wide Association Study of Smoking Behavior Traits in a Chinese Han Population - Li, Meng; Chen, Ying; Yao, Jianhua; Lu, Sheming; Guan, Ying; Xu, Yuqiong; Liu, Qiang; Sun, Silong; Mi, Qili; Mei, Junpu; Li, Xuemei; Miao, Mingming; et al. (Frontiers in Psychiatry, 2020)
Tobacco use is one of the leading causes of preventable disease worldwide. Genetic studies have elucidated numerous smoking-associated risk loci in American and European populations. However, genetic determinants for cigarette smoking in Chinese populations are under investigated. In this study, a whole-genome sequencing (WGS)-based genome-wide association study (GWAS) was performed in a Chinese Han population comprising 620 smokers and 564 nonsmokers. 13 single-nucleotide polymorphisms (SNPs) of the Raftlin lipid linker 1 (RFTN1) gene achieved genome-wide significance levels (P < 5 x 10-8) for smoking initiation. The rs139753473 from RFTN1 and six other suggestively significant loci from CUB and Sushi Multiple Domains 1 (CSMD1) gene were also associated with cigarettes per day (CPD) in an independent Chinese sample consisting of 1329 subjects (805 smokers and 524 nonsmokers). When treating males separately, associations between smoking initiation and PCAT5/ANKRD30A, two genes involved in cancer development, were identified and replicated. Within RFTN1, two haplotypes (i.e., C-A-C-G and A-G-T-C) formed by rs796812630-rs796584733-rs796349027-rs879511366 and three haplotypes (i.e., T-T-C-C-C, T-T-A-T-T and C-A-A-T-T) formed by rs879401109-rs879453873-rs75180423-rs541378415-rs796757175 were strongly associated with smoking initiation. In addition, we also revealed two haplotypes (i.e., C-A-G-G and T-C-T-T derived from rs4875371-rs4875372-rs17070935-rs11991366) in CSMD1 gene showing significant association with smoking initiation. Further bioinformatics functional assessment suggests that RFTN1 might participate in smoking behavior through modulating immune responses or interactions with the glucocorticoid receptor alpha and the androgen receptor. Together, our results may help understand the mechanisms underlying smoking behavior in the Chinese Han population.